Downregulated regulatory T cell function is associated with increased peptic ulcer in Helicobacter pylori-infection. (September 2017) - Bagheri, Nader; Shirzad, Hedayatollah; Elahi, Shokrollah; Azadegan-Dehkordi, Fatemeh; Rahimian, Ghorbanali; Shafigh, Mohammedhadi; Rashidii, Reza; Sarafnejad, Abdulfatah; Rafieian-Kopaei, Mahmoud; Faridani, Rana; Tahmasbi, Kamran; Kheiri, Soleiman; et al.
Abstract: Background: Helicobacter pylori ( H. pylori ) chronically colonizes gastric/duodenal mucosa and induces gastroduodenal disease such as gastritis and peptic ulcer and induces vigorous innate and specific immune responses; however, the infection is not removed, a state of chronic active gastritis persists for life if untreated. The objective of this study was to determine the number of regulatory T cells (Tregs) in gastric mucosa of patients with gastritis and peptic ulcer and determined the relationship between main virulence factor of H. pylori and Tregs. Methods and materials: A total of 89 patients with gastritis, 63 patients with peptic ulcer and 40 healthy, H. pylori -negative subjects were enrolled in this study. Expression of CD4 and Foxp3 was determined by immunohistochemistry. Antrum biopsy was obtained for detection of H. pylori, bacterial virulence factors and histopathological assessments. TGF-β1, IL-10 and FOXP3 expressions were determined by real-time polymerase chain reaction (qPCR). Results: The numbers of CD4 + and Foxp3 + T cells as well as the expression of IL-10, TGF-β1, FOXP3, INF-γ and IL-17A in infected patients were significantly higher than the ones in uninfected patients. Also, the number of CD4 + T cells was independent on the vacuolating cytotoxin A (vacA) and outer inflammatory protein A (oipA), but it was positively correlated with cytotoxin-associated gene A (cagA). Instead, the number of Foxp3 + T cells was dependent on the vacA and oipA, but it was independent on cagA. The number of Foxp3 + T cells and the expression of IL-10, TGF-β1 and FOXP3 in infected patients with gastritis were significantly higher than the ones in infected patients with peptic ulcer. Moreover, the number of CD4 + T cells and the expression of IL-17A and INF-γ was the lowest in the gastritis patients, however, increased progressively in the peptic ulcer patients. Additionally, the numbers of CD4 + and Foxp3 + T cells as well as the expression of IL-10, TGF-β1, FOXP3 and INF-γ were positively correlated with the degree of H. pylori density and chronic inflammation. Conclusion: Tregs are positively associated with vacA alleles and oipA status of H. pylori and histological grade but negatively associated with peptic ulcer disease. Highlights: The number of CD4 and Treg cells in infected patients had a significantly higher than uninfected. The number of CD4 cells was independent on vacA and oipA, but it was positively correlated with cagA. The number of Tregs was dependent on the vacA and oipA, but it was independent on cagA. The number of CD4 + cells was lowest in the gastritis patients. The number of Tregs in infected patients with gastritis were significantly higher.